Natural history of low back pain. A longitudinal study in nurses. - Smedley, J; Inskip, H; Cooper, C; Coggon, D (1998)
STUDY DESIGN: Longitudinal study. OBJECTIVES: To assess the natural history of low back pain. SUMMARY OF BACKGROUND DATA: Most episodes of low back pain resolve or improve within a few weeks, but chronic or recurrent symptoms are common. Previous studies of natural history have usually relied on people's long-term recall of symptoms, or they have been limited to patients seeking clinical care. METHODS: Nurses (1,165 women) completed a baseline questionnaire and up to eight follow-up questionnaires 3 months apart. Each questionnaire asked whether they had experienced low back pain in the past month. One-month prevalences of pain at specified follow-ups were calculated according to histories of pain reported on earlier questionnaires. RESULTS: The 1-month prevalence of low back pain at individual follow-ups ranged from 16% to 19%. Of 906 women who completed the baseline questionnaire and at least three follow-up questionnaires, 38 (4.2%) reported pain every time they returned a questionnaire, and 190 (21.0%) reported pain on at least three occasions. The presence or absence of low back pain at baseline was highly predictive of future pain throughout follow-up. The longer that back pain was consistently reported, the more likely it was to be present at the next follow-up. Later risk was lowest in women who reported no back pain at baseline or either of the first two follow-ups. Back pain carried a worse prognosis if it was disabling or associated with sciatica. CONCLUSIONS: Our results confirm the importance of back pain duration and the occurrence of associated disability and sciatica as predictors of future symptoms, and allow more reliable quantification of the natural history of back pain in women of working age. In the absence of other information, the differentials in risk associated with a person's history of back pain appear to remain constant for a period of at least 2 years.